Extensive perinephric abscess complicated by herpes simplex virus 1 reactivation. Issue 4 (30th March 2010) - Alleyne, SA; Bukhari, SS; Fraser, M; Spiers, P
Abstract : A 43-year-old man, admitted with a swollen right thigh, was diagnosed with a deep vein thrombosis. On day 6 he became septic. A CT scan demonstrated a right-sided hydronephrosis and a large retroperitoneal collection. Blood cultures and perinephric pus grew Escherichia coli resistant to amoxicillin only. On day 12 a vesicular rash appeared on the neck and herpes simplex virus 1 (HSV-1) grew on culture. On day 15 an upper leg collection was seen on CT scan. Thigh tissue specimens grew extended-spectrum β-lactamase (ESBL) producing E coli and HSV-1 was also detected by polymerase chain reaction in the tissue. On day 18 the patient died. This case illustrates an unusual presentation and complication of a perinephric abscess. In critically ill patients herpes simplex reactivation and emergence of multiresistant organisms may occur resulting in treatment failure.